If the function f(x) = 1 + sinπx2, for&nbs

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

941.

If y = tan-1sinx + cosxcosx - sinx, then dydx is equal to

  • 1/2

  • 0

  • π4

  • 1


942.

The derivative of cos-12x2 - 1 w.r.t. cos-1x is

  • 1 - x2

  • 2x

  • 121 - x2

  • 2


943.

The value of c in mean value theorem for the function f(x) = x2 in [2, 4] is

  • 3

  • 7/2

  • 4

  • 2


Advertisement

944.

If the function f(x) = 1 + sinπx2, for -  < x  1ax +b,           for 1 < x <36tanπx12,      for 3  x < 6 is continuous in the interval (- , 6), then the values of a and b are respectively

  • 0, 2

  • 1, 1

  • 2, 0

  • 2, 1


C.

2, 0

Given, fx = 1 + sinπx2, for -  < x  1ax +b,           for 1 < x <36tanπx12,      for 3  x < 6and f(x) is continuous in the mterval (- , 6).Therefore, f(x) will be continuous at x = 1 and at x= 3.For continuity at x = 1                      f1 = limx1fx   1 + sinπ4 = limx1ax +b             a +b = 2           ...iFor continuity at x= 3                     f3 = limx3fx        6tanπ2 = limx3ax +b          3a +b = 2           ...iiOn solving Eqs. (i) and (ii), we get

         a = 2, b = 0


Advertisement
Advertisement
945.

The value of m for which the function f(x) = mx2, x  1  2x, x > 1, is differentiable at x = 1, is

  • 0

  • 1

  • 2

  • does not exist


946.

If y = (1 + x1/4)(1 + x1/2)(1 - x1/4), then dy/dx is equal to

  • 1

  • - 1

  • x

  • x


947.

If y = loglogx, then eydydx is equal to

  • 1xlogx

  • 1x

  • 1logx

  • ey


948.

For the function f(x) = x2 - 6x + 8, 2  x  4, the value of x for which f'(x) vanishes, is

  • 9/4

  • 5/2

  • 3

  • 7/2


Advertisement
949.

If y = x + 1 + x2n, then 1 + x2d2ydx2 + xdydx is equal to

  • n2y

  • - n2y

  • - y

  • 2x2y


950.

If xy = ex - y, then dydx is

  • 1 + x1 + logx

  • 1 - logx1 + logx

  • not defined

  • logx1 + logx2


Advertisement